Spontaneous expulsion of a bronchial foreign body / Addina Mohd Baki ... [et al.] - Mohd Baki, Addina; Che Mohd Amin, Anis; Ali, Ahmad Hafiz; Mohamad, Irfan (Faculty of Medicine, 2021)
Foreign body aspirations represent a life-threatening emergency and continue to pose challenges to the otorhinolaryngology team. The mainstay of treatment remains bronchoscopy, and early removal should be performed to prevent complications. Spontaneous expulsion of an airway foreign body is a rare entity with few cases reported. Additionally, its occurrence and associated complications are still unclear. Besides, an expelled foreign body can be swallowed, migrate to another location, or lodge in a subglottic area. We are reporting an unusual case of a young man who accidentally inhaled a thumb pin. However, the foreign body was expelled without any complications after he suddenly had a severe bout of cough.